An EPR and DFT study on the primary radical formed in hydroxylation reactions of 2, 6-dimethoxy-1, 4-benzoquinone. (17th June 2016) - Haeri, Haleh H.; Bogeski, Ivan; Gulaboski, Rubin; Mirceski, Valentin; Hoth, Markus; Kappl, Reinhard
ABSTRACT: The quinone compound 2, 6-dimethoxy-1, 4-benzoquinone is hydroxylated in alkaline aqueous solution with pH above 12. Electron paramagnetic resonance experiments showed that two transient radicals are formed in this reaction. The radical appearing first is assigned to a one electron reduced 2, 6-dimethoxy-1, 4-benzoquinone, receiving the electron from an intermediate anionic hydroxylated species. For this primary radical, all proton couplings were determined (quinoid ring protons: 1.453 G, methyl protons: 0.795 G). The density functional theory method was applied to obtain electronic and structural information of the primary radical and a solution structure is suggested. For approaching the experimental hyperfine couplings in theoretical models, it was necessary to consider effects of external polarisation arising from water molecules near one carbonyl group, and the orientation of methoxy groups towards the quinone ring. With this approach, the secondary radical formed in the hydroxylation reaction, and the transient radicals found for other biologically important quinones (including coenzymes Q) and their hydroxylated species may become accessible. Abstract :